Reading Nature as Revelation: A Sufi-Based Ecotheological Interpretation of the Qur’ān in the Context of Global Ecological Crisis - Sakti, M. Nawa Syarif Fajar; Afwan, Muhammad Nur; Qudsiyah, Bagus Haziratul; Hidayaturrohmah, Nur; Anwar, Khoerul; Masruroh, Fina Lailatul; Taufiqurrahman, Muhammad; Maulana, Muhamad (Journal of Islamic Thought and Civilization, 2026)
This article offers a Sufi-based ecotheological interpretation of the Qur’ān by positioning nature (al-‘ālam) as a living revelation (āyah kauniyyah) and a manifestation (tajallī) of God. In light of the global ecological crisis, this study reframes the human-nature relationship through a sufi hermeneutic. Drawing on the cosmology of Ibn ‘Arabi and the metaphysical critique of Seyyed Hossein Nasr, it argues that nature functions as a mirror through which God reveals Himself. Thus, environmental destruction becomes not only ecological damage, but a rupture in spiritual awareness and Divine connection. Using qualitative library research, this study employs thematic Qur’ānic exegesis (tafsīr maudhū‘ī) supported by Sufi hermeneutics. It interprets selected āyāt not merely through ethical or scientific lenses, but symbolically, emphasizing their spiritual dimensions. The dual identity of the human as ‘abd (servant) and khalīfah (vicegerent) is explored to show that ecological responsibility is rooted in both ethical duty and ontological design. This approach contributes a novel perspective in Islamic environmental thought by highlighting ecology as a spiritual path toward ma‘rifah (gnosis). It presents ecological awareness not just as stewardship, but as a form of worship and remembrance. The article concludes that a Sufi interpretation approach can offer a transformative vision for restoring sacred relations between God, humanity, and nature.